Nanai argument structure: Russian influence - Shagal, Ksenia (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2013)
The paper investigates two classes of verbs in the Naikhin dialect of Nanai (Tungusic; spoken mostly in the Russian Far East) that demonstrate a certain instability with respect to their argument structure in a situation where there is contact with Russian, the dominating language of the region. The avalent verbs tend to acquire a subject, thus turning into intransitives, while ditransitive verbs reduce the original number of possible argument encoding strategies and preserve the dative-accusative pattern only. The general claim of this article is that although there might be some other reasons (structural, typological, etc.) for the argument structure change in an endangered language, language contact also contributes to the process.